Discovery of novel inhibitors of ribosome biogenesis by innovative high throughput screening strategies. Issue 15 (9th August 2019) - Scull, Catherine E.; Zhang, Yinfeng; Tower, Nichole; Rasmussen, Lynn; Padmalayam, Indira; Hunter, Robert; Zhai, Ling; Bostwick, Robert; Schneider, David A.
Abstract : Over the past two decades, ribosome biogenesis has emerged as an attractive target for cancer treatment. In this study, two high-throughput screens were used to identify ribosome biogenesis inhibitors. Our primary screen made use of the HaloTag selective labeling strategy to identify compounds that decreased the abundance of newly synthesized ribosomes in A375 malignant melanoma cells. This screen identified 5786 hit compounds. A subset of those initial hit compounds were tested using a secondary screen that directly measured pre-ribosomal RNA (pre-rRNA) abundance as a reporter of rRNA synthesis rate, using quantitative RT-PCR. From the secondary screen, we identified two structurally related compounds that are potent inhibitors of rRNA synthesis. These two compounds, Ribosome Biogenesis Inhibitors 1 and 2 (RBI1 and RBI2), induce a substantial decrease in the viability of A375 cells, comparable to the previously published ribosome biogenesis inhibitor CX-5461. Anchorage-independent cell growth assays further confirmed that RBI2 inhibits cell growth and proliferation. Thus, the RBI compounds have promising properties for further development as potential cancer chemotherapeutics.